Sustaining our Spirits: Spiritual Study/Discussion Groups For Coping with Medical Illness - Meyerstein, Israela (Journal of religion and health, 2005)
Illness is a universal experience that evokes a range of difficult emotions and tough spiritual questions, often without satisfying answers. Illness can be alienating and isolating. Sustaining one's spirits and preserving identity in the face of illness is a challenge for patients, family members, and caregivers. This paper introduces Spiritual study/discussion groups to strengthen patients' perceived coping with illness. The groups introduce a spiritual perspective, provide emotional support, and offer a variety of "spiritual coping tools," utilizing traditional and contemporary resources. Preliminary evaluations suggest that a "healing" time and space is created through the provision of comfort, connection, support, and inspiration.